Association between residential green cover and direct healthcare costs in Northern California: An individual level analysis of 5 million persons. (May 2022) - Van Den Eeden, Stephen K.; H.E.M. Browning, Matthew; Becker, Douglas A.; Shan, Jun; Alexeeff, Stacey E.; Thomas Ray, G.; Quesenberry, Charles P.; Kuo, Ming
Highlights: Included over 5 million members of Kaiser Permanente Northern California. Determined direct health care costs for all of these individuals from 2003 to 2015. Used residential Normalized Difference Vegetation Index (NDVI) satellite data to determine the green cover of each individual. Conducted log-linear gamma generalized linear regression to determine the association between green cover and health care costs. Living in areas of high green cover was inversely associated with total direct health care costs. Abstract: Background and objective: Prior studies have shown higher green cover levels are associated with beneficial health outcomes. We sought to determine if residential green cover was also associated with direct healthcare costs. Methods: We linked residential Normalized Difference Vegetation Index (NDVI) satellite data for 5, 189, 303 members of Kaiser Permanente Northern California (KPNC) to direct individual healthcare costs for 2003–2015. Using generalized linear regression to adjust for confounding, we examined the association between direct healthcare costs and green cover within 250, 500, and 1000 meters (m) of an individual's residence. Costs were determined from an internal cost accounting system that captures administrative and patient care costs for each clinical encounter. Sensitivity analyses included adjustments for comorbidity and an alternative measure of green cover, tree canopy. Results: We observed a significant inverse association between higher levels of residential green cover and lower direct healthcare costs. The relative rate of total cost for the highest compared to the lowest decile of NDVI was 0.92 (95% CI 0.90–0.93) for the 500 m buffer. The association was robust to adjustment from a broad array of confounders, found at each buffer size, and largely driven by hospitalization, and emergency department visits. Individuals in the top decile of residential green cover had adjusted healthcare costs of $374.04 (95% CI $307.31-$439.41) per person per year less than individuals living in the bottom or least green decile. Sensitivity analyses including tree canopy cover as the green space measure yielded similar findings. Analyses that included adjustment for comorbidity were consistent with the hypothesis that green cover reduces healthcare costs by improving health status. Conclusion: Green cover was associated with lower direct healthcare costs, raising the possibility that residential greening can have a significant healthcare cost impact across the population.